Internalisasi Nilai Moderasi Beragama Dalam Membentuk Toleransi Siswa - Rokib, Moh; Buna’i; Maimun (Kartika: Jurnal Studi Keislaman, 2025)
The internalization of the value of religious moderation is the process of instilling the values of tolerance, balance, justice, and respect for diversity in individuals or groups, which aims to form moderate awareness and behavior. This research focuses on the process and implications of internalizing the value of religious moderation in shaping student tolerance at SD Catholic Santo Redemptus and SDN Lawangan Daya II Pamekasan, with a qualitative approach of multi-site case study type. Data were collected through semi-structured interviews, non-participant observations, and documentation, then analyzed through the stages of data condensation, presentation, and conclusion drawn, and tested for validity through credibility, transferability, dependability, and objectivity tests. The results of the study show that the internalization of the value of moderation is carried out through classroom learning, extracurricular activities, local cultural preservation, and out-of-class learning (in Catholic Elementary Schools), with stages of transformation, transaction, and transinternalization. Teachers integrate values such as tawassuth, i'tidal, tasamuh, and muwathanah into civil society and religious lessons, as well as encourage deliberation and appreciation of differences. Joint ceremonial activities, joint scouts, masses, bureauthals, the use of Madurese traditional clothing, and visits to places of worship, strengthen the inclusive character and tolerant attitude of students in daily life.